Growth, productivity and quality of male sterile baby corn (Zea mays) hybrid under varying nitrogen levels and timings of detasseling - NITHINKUMAR, KADAGONDA; Singh, S P; PRAKASH, VED; BAGRECHA, SHREYAS; SAIKIA, NILUTPAL; DASS, ANCHAL; DOLINA DEVI, AYEKPAM; AR, DEVIKA (The Indian Journal of Agricultural Sciences, 2025)
The present study was conducted at Institute of Agricultural Sciences, Banaras Hindu University, Varanasi during the winter (rabi) season of 2021–2022 to determine effect of different levels of nitrogen and detasseling time on picking-wise productivity and quality of baby corn. The results revealed that detasseling immediately after tassel emergence significantly higher four pickings of husked and dehusked baby corn yield (10.6–38.5% and 15.7–44.2%, respectively increased), and carbohydrates, starch and sugars over the no detasseling, but at par with detasseling at 7 days after tassel emergence. Similarly, the 200 kg N/ha increased the plant height, no. of leaves/plant, LAI, SPAD, four pickings of husked and dehusked baby corn yield (46.9–156.2% and 44.16–152.48%), respectively increased), and carbohydrates, starch and sugars over the 50 and 100 kg N/ha, however, at par with 150 kg N/ha. Overall, this experimental study recommended that detasseling immediately after tassel emergence combined with 200 kg N/ha increased the growth characteristics, yield and quality parameters of male-sterile baby corn in the Varanasi region of Uttar Pradesh.